2019
DOI: 10.24874/ti.2019.41.02.13
|View full text |Cite
|
Sign up to set email alerts
|

Friction and Wear of Cr-O-N Coatings Characterized by Atomic Force Microscopy

Abstract: Cr-O-N coatings with different oxygen concentration were deposited using vacuum arc plasma fluxes on steel substrates. The coatings were investigated using atomic force microscopy under ambient temperature and humidity controlled conditions. The surface structure, friction and wear were investigated. The results indicate that coefficient of friction and friction force of Cr-O(50)-N coating consisted of Cr2O3 phase tested in a sliding regime are the lowest compared to other Cr-O-N coatings characterized by cubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Research by Noel et al 69 explored the wear of copper-based composites at the nano-scale using AFM and found that for higher loads in the region of tens of nano-newtons, ‘Archard-like’ wear was observed. Similarly, Kuznetsova et al 70 used AFM to examine the friction and wear of Cr–O–N coatings at the nano-scale under similar loads to Noel et al and made similar observations. Considering similarities between these works and the work presented in the current paper, it is believed that the Archard law would be one of applicable methods to conduct a multi-scale transient wear prediction as further study.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Research by Noel et al 69 explored the wear of copper-based composites at the nano-scale using AFM and found that for higher loads in the region of tens of nano-newtons, ‘Archard-like’ wear was observed. Similarly, Kuznetsova et al 70 used AFM to examine the friction and wear of Cr–O–N coatings at the nano-scale under similar loads to Noel et al and made similar observations. Considering similarities between these works and the work presented in the current paper, it is believed that the Archard law would be one of applicable methods to conduct a multi-scale transient wear prediction as further study.…”
Section: Resultsmentioning
confidence: 77%
“…Similarly, Kuznetsova et al 70 used AFM to examine the friction and wear of Cr-O-N coatings at the nanoscale under similar loads to Noel et al and made similar observations. Considering similarities between these works and the work presented in the current paper, it is believed that the Archard law would be one of applicable methods to conduct a multi-scale transient wear prediction as further study.…”
Section: Wear Resistancementioning
confidence: 76%
“…The volume of wear V was estimated by the cross-sectional area and the perimeter of the wear track [ 47 ].…”
Section: Methodsmentioning
confidence: 99%